Educational Impacts of Chess Instruction in Azerbaijan. - Zeynalli, Aytan (ADA University, 2015)
Does chess instruction improve mathematical and reading achievements of school students in Azerbaijan? The results in national and international examinations such as the Programme for International Students Assessment (PISA), and the Students State Admission Commission (SSAC), tests have shown that school students in Azerbaijan are performing at a lower level. This paper intends to propose chess instruction in schools as a new approach and possible solution to this problem. The study presented in this thesis explores the educational effects of chess instruction on academic achievement, especially mathematical and reading abilities among primary school students in Azerbaijan. T-tests have been conducted among first, second and third grade (chess and non chess groups) students from two schools in Baku. The results obtained from t- tests indicate that there is an improvement in reading outcomes among second and third grade chess group students. Nevertheless, there is inconsistency in the results of mathematical attainments of students in that only second graders show an improvement in their achievements. In addition, other t- test results indicate that changes in pretest performances in math and reading were not different from changes in the post test performances in first and third grade students. However, these findings suggest that further research is needed to conduct and examine the educational impacts of chess instruction in more detail in the case of Azerbaijan.
Keywords: Public and International Affairs; Chess instruction; PISA; SSAC test; Academic outcomes; Mathematics and reading attainments